The town of York, 1793-1815 a collection of documents of early Toronto. - Firth, Edith G., 1927- (Ontario series, 1962)
This volume, the fifth of the Ontario Series of the Champlain Society, tells the history of the town of York (Toronto) from the arrival of John Graves Simcoe in 1793 through the war of 1812 until news of the peace reached the town in the spring of 1815. The selection of contemporary documents attempts to show why York was chosen for a settlement in the first place, the kind of community that developed, and the effect of the War on that community. Apart from the normal problems connected with the establishment of any settlement, the officials of the town of York were faced with the necessity of creating a worthy capital city for Upper Canada at a time when Kingston because of its pre-eminence as the military and naval centre of the province and its commercial prosperity overshadowed all other settlements. The book also illustrates the gradual integration into a corporate body of many diverse elements--senior government officials, discharged soldiers, tradesmen, labourers--so that by 1815 the characteristics of modern Toronto were beginning to be evident in York. This collection of documents and the editor's Introduction will provide the student of local history with a good deal of primary material and the general reader with an interesting account of the early years of the modern metropolis of Toronto. Vol. V, Ontario Series, Champlain Society.